The Effect of Work From Home, Digital Platform and Digital Literacy on Employee Productivity at PT. XYZ Cirebon Regency - Nurwidyani, Sabrina Eka; Jaya, Rama Chandra; Utami, Widyastuti Nurmalia; Mubarok, Dadan Abdul Aziz; Ismail, Gurawan Dayona (Dinasti International Journal of Management Science, 2024)
This study aims to test and analyze the effect of work from home, digital platforms and digital literacy on work productivity at PT XYZ Cirebon Regency partially or simultaneously. This research is a quantitative study with a population of 35 employees and uses non-probability sampling techniques, so that the sample size uses the entire population. The data sources used are primary data and secondary data processed with the help of SPSS 26.0 for windows. The data analysis technique used is multiple linear regression. Based on the partial test results, work from home and digital platforms have a positive and significant effect, while digital literacy has a positive but insignificant effect on the work productivity of employees of PT XYZ Cirebon Regency. In simultaneous testing work from home, digital platform and digital literacy together have a positive and significant effect on the work productivity of employees of PT. XYZ Cirebon Regency. The coefficient of determination shows that work from home, digital platform and digital literacy are able to explain the contribution of work from home, digital platform and digital literacy to the work productivity of employees of PT. XYZ Cirebon Regency, which is 98.1%, while the remaining 1.9% is influenced by other variables outside this regression equation or variables not examined.